Eggshell Water Vapor Conductance and Shell Structural Characteristics of Broiler Breeder in Different Flock Ages - Ümran Şahan; Saliha Sabah; Arda Sözcü (Journal of Agricultural Sciences)
The aim of the study was to investigate eggshell traits; including eggshell water vapor conductance, eggshell thickness, pore density, egg weight loss as well as eggshell surface area and volume in 28 and 40 week-old broiler breeders. Furthermore, the phenotypic correlations among the eggshell characteristics were determined. The eggs were ranged from 54.41 g to 60.78 g and 54.71 g to 60.62 g in 28 and 40 wk-old age groups, respectively. All eggs were weighed and numbered before setting and were monitored individually until the end of the incubation. Mean eggshell water vapor conductance (G) value was 11.00±1.01 mg H2O day-1 torr-1 in 28 wk-old flock and 11.99±1.28 mg H2O day-1 torr-1 in 40 wk-old flock respectively (P<0.05). The mean value of shell thickness and pore density mean along with the two regions (broad end and equator) were higher and significant in 28 wk-old flock (P<0.01). Egg weight loss was not found to be significant. Surface area was higher in 40 wk-old flock while as volume was higher in 28 wk-old flocks (P<0.01). There was no correlation between eggshell thickness and pore density. Both eggshell thickness and pore density were having significant positive correlation along with three eggshell regions in each flock ages (P<0.01).